Peningkatan Hasil Belajar Siswa Pada Pembelajaran PKn Menggunakan Model Kooperatif Tipe Group Investigation - Crestella, Dea; Muhammadi, Muhammadi; Alwi, Elma (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
The purpose of the research was to improve the students learning outcomes on the civic education by using cooperative model type Group Investigation. This research is a classroom action research using qualitative and quantitative approach. Research procedure: planning, implementation, observation and reflection. The subject of the research was the teacher and the student in grade V of the SDN 16 Campago Ipuh. From cycle I to cycle II, the score of the lesson plan from 78,57% (Good) to 92,85% (Very Good). The teachers activities from 75% (Enough) to 87,5% (Very Good). The students activities from 75% (Enough) to 87,5% (Very Good). Students learning outcomes from 74,4 (Enough) to 86,6 (Very Good). Based on these result, it was concluded that the use of cooperative model type Group Investigation could increase the students learning outcomes on the civic education.Keywords : learning outcomes on the civic education, group investigation